Analysis of the maximum shot velocity in terms of accuracy intention in soccer players - D. Juárez; F. Navarro (Asociación Española de Ciencias del Deporte, 2010)
In this study, we analyzed the relation between maximum shot velocity with and without accuracy intention in soccer players (N= 108; 70 soccer players and 38 indoor soccer players), and how this accuracy can affect to maximum shot velocity. We found an moderate-high correlation between with and without accuracy intention shots (0,76; ρ<0,01), what suggests the existence of a tendency that soccer players that kicked faster without accuracy intention, did also kick faster with accuracy intention. On the other hand, we found significant differences in both velocities (28,355 ± 1,796 m/s and 27,001 ± 1,962 m/s with and without accuracy intention, respectively). In conclusion, we can say that accuracy intention means a significant reduction of maximum shot velocity. KEY WORDS: soccer, indoor soccer, shot, accuracy.